A Follow Up Study on Newly Detected Sputum Positive Pulmonary Tuberculosis Cases on Anti-Tubercular Treatment in Bijapur Taluk - Mahabalesh M Angadi; Sowmya Bhat; Haridas Somayaji; Arun P Jose (Medsci Publications, 2016)
Background: TB remains a challenge and major public health problem in 21st century, although there are treatment regimens that have a greater than 95% cure rate. This study was done to document the role of socio demographic profile in completing the schedule of treatment. Materials and Methods: A follow up study was conducted on 248 newly detected sputum positive tuberculosis cases. Each patient was visited 4 times during their treatment course. After obtaining oral consent, information was collected using a pre-tested ques- tionnaire. Data was analyzed using SPSS v.16. Results: In our study majority of the patients belonged to econom- ically productive age group of 21-50 years (67.34%). Cure rate was 81.85%, default rate was 5.64%. Main reasons for default were side effects of the drug and change of residence (28.57% each).There was no statistical association between socio- demographic factors and cure rate. Conclusion: Even though accessibility to DOT center was better in our study cure rate was less than the RNTCP norm of 85%. This can be attributed to high default rate.